JFQ volume 42 issue 4 Cover and Back matter (Journal of Financial and Quantitative Analysis, 2007)
There are no known bondholders, mortgagees, or other security holders owning or holding 1 percent or more of total amount of bonds, mortgages, or other securities. The purpose, function,